High cripto-1 and low miR-205 expression levels as prognostic markers in early stage non-small cell lung cancer. (February 2018) - Park, Kang-Seo; Moon, Yong Wha; Raffeld, Mark; Lee, Dae Ho; Wang, Yisong; Giaccone, Giuseppe
Highlights: We evaluated Cripto-1 and miR-205 expression by IHC and qPCR, respectively, in 265 resected NSCLC. We demonstrated that high cripto-1 expression correlates with poor prognosis in early NSCLC. Low miR-205 reduced by Cripto-1 expression is associated with poor prognosis in NSCLC patients. Abstract: Objectives: Cripto-1 (CR-1) plays a critical role in the activation of SMAD, SRC, and epithelial-to-mesenchymal transition (EMT) pathways and has been shown to be prognostic in several cancer types. In addition, we showed that CR-1 renders EGFR-mutated NSCLC cells resistant to EGFR-TKI through the activation of SRC and EMT via miR-205 downregulation. This study aimed to investigate the correlation between expression of CR-1 and miR-205 and prognosis of NSCLC patients with or without EGFR mutations. Materials and methods: A total of 265 patients with stage I (AJCC 6th edition) radically resected NSCLC were tested for CR-1 expression and EGFR mutations by immunohistochemistry and miR-205 expression via qPCR assay. Results: CR-1 expression was evaluated with immunohistochemistry using a tissue microarray on 265 T1-2N0 surgical NSCLC samples. Of the 265 tumors, 250 (94%) expressed various levels of CR-1. A significant inverse correlation was identified between expression of miR-205 and CR-1. NSCLC patients (T1N0, n = 106) with high CR-1 expression had worse prognosis (shorter recurrence-free survival, p = .045) than those with low CR-1 expression. A similar trend was observed in NSCLC patients with normal preoperative carcinoembryonic antigen (CEA) levels (serum CEA levels <5 ng/ml; n = 179; p = .085); however, no significant correlation was found between CR-1 expression and survival rate in the T2N0 or high CEA groups. In addition, NSCLC patients with low miR-205 expression (n = 126) had poorer prognosis in terms of recurrence than those with high miR-205 expression (n = 127; p = .001). Conclusion: High CR-1 expression is correlated with poor prognosis in NSCLC with low tumor burden and may be used to select high-risk patients for adjuvant chemotherapy in early NSCLC. Moreover, low miR-205 expression likely related to high CR-1 expression could be a prognostic marker for patients with NSCLC.